Analisis Kekuatan pada Pengembangan Desain Shelf pada Base Cabinet dengan Analisis Elemen Hingga menggunakan Perangkat Lunak Solidworks CAE - Bayu Prabandono; Rafael Bhima Sena Purnama Putra; Andronikus Cahya Pradana; Agus Kurniawan; Aditya Nugraha; Mirza Yusuf (Universitas Muhammadiyah Yogyakarta, 2024)
ATMI Duta Engineering company is a manufacturing company engaged in the field of sheet metal with a material cutting process using laser cutting technology. Sheet metal products produced at ATMI Duta Engineering company is very diverse, one of which is the base cabinet. The base cabinet has main components, one of which is the shelf. Based on the data obtained from the interview process, there are problems, namely the shelf has never been analyzed, there are no finished products, and there is a risk of damage due to excessive loading. The solution to the shelf problem is to carry out a shelf design analysis using the finite element analysis method through Solidworks CAE software. The CAE simulation was applied to 27 variations of the shelf design by combining 3 test variables, namely the shelf model, the reinforcement model, and the thickness of the material. The material used in the simulation is SPCC material with a thickness of 1mm, 1.2mm and 1.5mm. The CAE simulation results obtained are then compared with reference to the SEFA 8M-2016 standard. The loading given in the CAE simulation is ± 108 kg (1.2 SEFA standards). The strongest variation obtained from the elimination process is variation 19 with a combination of shelf model 1 design, reinforcement model A, and with a material thickness of 1.5mm. Variation 19 meets the SEFA 8M-2016 standard because the displacement value is 1.065mm and this value is smaller than 6.35mm.